2015
DOI: 10.1111/jfb.12706
|View full text |Cite
|
Sign up to set email alerts
|

Size‐selective feeding on phytoplankton by two morpho‐groups of the small freshwater fishAmblypharyngodon mola

Abstract: Two morpho-groups (i.e., small, MGS and big, MGL) of the small freshwater fish Amblypharyngodon mola were studied for their feeding behaviour in the natural environment. Both the morpho-groups fed on a variety of phytoplankton including Cyanophyceae, Chlorophyceae, Bacillariophyceae and Euglenophyceae. The fish had more Chlorophyceae and Bacillariophyceae in their gut than other phytoplankton. Costello's selectivity plots revealed that the MGS fed on the smaller phytoplankters (2-6 µm in size), whereas the MGL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…One reason for this difference could be that A. solandri, unlike tunas, often bite their prey into smaller pieces, which mitigates the need for size-specific prey selection. Prey size preferences in previous studies of fishes are often attributed to mouth morphometry (Conley & Hopkins, 2004) and size-selective feeding is described as a method to overcome gape-limitation in various species (Nandi & Saikia, 2015). While gape-limitation has not been measured in A. solandri, this study identified numerous large pieces of individual prey items in A. solandri stomachs, which illustrates the ability of these fish to consume larger organisms.…”
Section: P R E Y S I Z Ementioning
confidence: 60%
See 1 more Smart Citation
“…One reason for this difference could be that A. solandri, unlike tunas, often bite their prey into smaller pieces, which mitigates the need for size-specific prey selection. Prey size preferences in previous studies of fishes are often attributed to mouth morphometry (Conley & Hopkins, 2004) and size-selective feeding is described as a method to overcome gape-limitation in various species (Nandi & Saikia, 2015). While gape-limitation has not been measured in A. solandri, this study identified numerous large pieces of individual prey items in A. solandri stomachs, which illustrates the ability of these fish to consume larger organisms.…”
Section: P R E Y S I Z Ementioning
confidence: 60%
“…solandri , unlike tunas, often bite their prey into smaller pieces, which mitigates the need for size‐specific prey selection. Prey size preferences in previous studies of fishes are often attributed to mouth morphometry (Conley & Hopkins, ) and size‐selective feeding is described as a method to overcome gape‐limitation in various species (Nandi & Saikia, ). While gape‐limitation has not been measured in A .…”
Section: Discussionmentioning
confidence: 99%
“…This may be accounted for by the diversity of feeding resources (Pianka, ) and, as in the specific case of the present study, by the trophic plasticity of characin fish species (Lowe‐McConnell, ; Araujo‐Lima et al , ; Manna et al , ). Coexistence may also result in distinct morphological adaptations that reflect different ways of exploiting the available resources (Labropoulou & Eleftheriou, ; Russo et al , ; Nandi & Saikia, ). The Characidae is one of the most diverse groups of Neotropical fishes, with a variety of body forms and behavioural strategies related to the exploitation of different microhabitats and environmental conditions (Manna et al , , ; Marques et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In carnivorous fish, such size-selective feeding is largely gape limited (Trauemper & Lauer 2005). A recent study of freshwater herbivorous fish Amblypharyngodon mola Hamilton 1822 showed that smaller gape size is related to small-sized prey and larger gape size to both small-and big-sized prey (Nandi & Saikia 2015). Gape size can also indicate feeding pattern (e.g.…”
Section: Figure 4 (A) Costello's (1990) Graphical Plot For Predator Fmentioning
confidence: 99%
“…Morphologically, length of upper jaw and lower jaw or vertical and horizontal width of mouth and shape of the head region could be considered to explain why the fish categorically feeds on some sizes of food and not others. Gill pores can be added as additional feature in describing 'escape limiting point' of particulate food from mouth cavity (Nandi & Saikia 2015). There is a series of mathematical measures that give an estimation of gape size in fish (Table 1E).…”
Section: Figure 4 (A) Costello's (1990) Graphical Plot For Predator Fmentioning
confidence: 99%